Pre-transfusion detection and transfusion therapy of a patient with autoanti-B and cold agglutinin - YANG Linyu; CHEN LI; LI Zhongjun (Zhongguo shuxue zazhi)
[Objective] To identify the ABO blood group of a patient with rare B antigen-specific autoantibody with cold agglutinin, and evaluate the effect of blood transfusion. [Methods] Red blood cells of patient were washed with 37℃ physiological saline and treated with sulfhydryl reagent. ABO blood group antigen was detected by tube method and microcolumn gel method. After the cold agglutinin was removed by EDTA anticoagulant plasma absorbed by type O red blood cells at 4℃, the related blood group antibodies were detected by type B red blood cells absorbing and releasing liquid at 4℃. The blood transfusion effect of patients was evaluated by the changes of hemoglobin before and after transfusion, and their ABO blood group was continuously monitored. [Results] B antigen was detected in the positive setting of serological experiment, cold agglutinin was detected by absorption and elution of type O red blood cells, and anti-B antibody was detected by absorption and elution of type B red blood cells. That is, there was specific autoantibody against B antigen, and the antibody property was IgM. No adverse reactions occurred during the infusion of 3 U type O washed red blood cells and the infusion was effective. The patient was continuously followed for two months, and the forward and reverse blood group identification were consistent, both of which were type B. [Conclusion] According to the previous blood group identification results, serological identification and follow-up comprehensive analysis, the ABO blood group of the patient is type B, but there are transient high titer cold agglutinin and B antigen-specific autoantibodies.